Novel biallelic variants in COL7A1 cause recessive dystrophic epidermolysis bullosa - Neng Yang; Yongyi Ma; Hong Yao; Qing Chang; Victor Zhang; Zhiqing Liang; Xiongwei Cai (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Autosomal recessive dystrophic epidermolysis bullosa (RDEB) is an incurable and severe inherited skin disorder characterized by recurrent blistering at the sublamina densa beneath the cutaneous basement membrane. It is caused by biallelic loss‐of‐function mutation in the gene encoding type VII collagen (COL7A1). This study aimed to identify the causative variants of a Chinese RDEB patient and further provide prenatal diagnosis for the ongoing risk pregnancy of the proband's mother. Methods Clinical exome sequencing (CES) has been performed and an in‐house pipeline was used to conduct a phenotype‐driven data analysis. A minigene assay was used to verify the pathogenicity of a novel splice site variant in the COL7A1. Results Here we report two compound heterozygous variants in COL7A1, c.3867delT (p.G1290Efs*35) and c.5532+4_5532+5delAG, identified in a RDEB patient by CES. The minigene assay confirmed that thec.5532+4_5532+5delAGchange was a noncanonic splice site variant leading to in an in‐frame deletion of exon 64. Prenatal diagnosis indicated that the present pregnancy of the patient's mother was not affected. Conclusion Our study expands the mutation spectrum of COL7A1 and demonstrated that CES and minigene assays were efficient tools for RDEB molecular diagnoses.